Digital Leadership for Sustainability: An Integrated Framework for Organizational Learning, Resilience, and Social Value Creation - Tathavadekar, Viraj P.; Nitin R. Mahankale (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
The framework intended to provide a broader view of sustainable leadership development in digital learning organizations, considering the global need for leaders who coordinate technological innovation with environmental and social inclusivity. The design and method of the framework tend to have a multidimensional package, working between theoretical analysis and the application of implementation strategies, analyzing contemporary organizational challenges alongside stakeholder methods and approaches for sustainability integration. The framework comprises four volumes: Digital Leadership Competencies, Sustainability Integration, Organizational Learning Adaptation, and Stakeholder Engagement Partnerships. The organizations practicing these approaches have become flexible and innovative through an increase in social impact and enjoy job satisfaction in the process. The paper proposes an original framework, systematically linking digital transformation capabilities to sustainability leadership, and offers ways to train leaders who can address complex contemporary issues and promote UN Sustainable Development Goals. The framework literally guides organizations and HR in building a leadership style that sustains organizational performance and generates a higher social impact. Its implementation supports community development through stakeholder engagement and inclusivity. Since the framework never had empirical support, its generalizability remains to be tested in industry-specific studies.